Eating disorders in adolescents with IDDM. A controlled study. - Peveler, R; Fairburn, C; Boller, I; Dunger, D (1992)
OBJECTIVE: To determine the prevalence of clinical eating disorders and lesser degrees of disturbed eating in adolescents with IDDM and a matched sample of nondiabetic control subjects. RESEARCH DESIGN AND METHODS: A cross-sectional survey of eating habits and attitudes conducted in 76 adolescents with IDDM, and age- and sex-matched nondiabetic control subjects. Eating disorder features were assessed by standardized research interview adapted for use with patients with diabetes (EDE). Glycemic control was assessed by GHb assay. RESULTS: Adolescent girls with IDDM were heavier than nondiabetic female control subjects and were dieting more intensively to control their shape and weight. However, clinical eating disorders were no more common among adolescent girls with IDDM than among nondiabetic control subjects. Nine percent of the IDDM girls met diagnostic criteria for an operational version of "Eating disorder not otherwise specified." Fifteen percent had omitted or reduced their dose of insulin to influence their shape and weight. Eating disorder features and insulin misuse for shape and weight control were not found in IDDM or nondiabetic boys, and these two groups did not differ in their body weight. CONCLUSIONS: Adolescent girls with IDDM are heavier than their nondiabetic counterparts and diet more intensively to control their shape and weight. Disordered eating habits and weight control behavior are common, but no more so in IDDM than in nondiabetic subjects. Insulin misuse for the purpose of shape and weight control is not restricted to subjects with a clinical eating disorder. Disordered eating is associated with impaired glycemic control.